The diffusion of agricultural technologies within social networks: Evidence from composting in Mali - Beaman, Lori; Dillon, Andrew (International Food Policy Research Institute, 2014)
This policy note summarizes research on the effect of social network characteristics and gender on the diffusion of information about an agricultural technology.